EMU – “Optimum” or “Viable” Currency Area? - Bucur, Andreea (Studies and Scientific Researches. Economics Edition, 2012)
Although the increasing heterogeneity as an effect of European Union enlargement, referring especially to the last two waves, is perceived as a single internal market and also euro single currency risk, European Monetary Union represents an important step towards deepening economic integration. Controversy on the Optimum Currency Area issue has created difficulties in empirical research effort to find appropriate responses to the EMU dilemma: is Euro zone an „optimum” or rather “viable” currency area?